The Utilization of Inferior Tree Species and Logging Wastes in the Moist Sub-tropical Forests of Eastern India - Chaudhuri, K. N. (Indian Forester, 1952)
The efficient utilization of the moist sub-tropical forests of Eastern India has so far been one of the most baffling problems in our forestry practice, due to the preponderance of numerous hardwood species that have either no value as timber at all, or are so low grade that their extraction usually does not pay. The few useful species that occur are again so scattered in distribution that their extraction is likewise very often uneconomic. The enormous wood waste, which is estimated to be about 10,000 tons (50 c.ft.each) annually in North Bengal with only about two-thirds of the prescribed clear-felling done at present, and obviously several times as much in Assam, is to-day regularly burnt in the clear-felling areas, or left in the forest to rot elsewhere. The best way to utilize these inferior species, and logging wastes including thinnings in many cases would appear to be some form of chemical conversion whereby the value of the wood substance is so appreciably increased as not only to cover the costs of extraction, processing and subsequent transport to the markets, but also to give an end product which has a steady or rising demand in the country. Various methods of chemical utilization of wood waste, including carbonization and destructive distillation, other forms of wood distillation, pulping for paper, manufacture of fibreboards, hydrolysis to produce sugar and ethyl alcohol and the use of wood waste in the plastics industry, etc., are considered and their applicability in this region is discussed both from technical as well as from economic points of view. It is concluded that the manufacture of various kinds of hard fibreboards in decentralized plants such as are now in operation in many of the Central European countries and in the U.S.A., is likely to be one of immediate and wide applicability in this area. There is no scope of destructive distillation on a conventional scale as a profitable undertaking, due to the very generally doubtful economic prospects of byproduct recovery and to the rather limited local demand of charcoal which is the main end product in this method of utilization. To meet the existing regional demand of charcoal for domestic use by the few hill towns, carbonization in native kilns should be continued with partial recovery of byproducts with inexpensive equipments that have recently been evolved in China, if the latter proves profitable. A new demand for charcoal high in carbon content and free from tar, such as can only be produced in retorts under controlled conditions, for use in specialized chemical industries like case-hardening, activated carbon and production of carbon bisulphide is slowly developing; this may eventually permit or necessitate the operation of smaller distillation units in certain localities, usually without recovery of byproducts, as have recently been evolved in Switzerland and U.S.A. The potentialities of several other methods, viz., special forms of hardwood distillation for the manufacture of nitrogenous fertilizers ( through the synthesis of Ammonia) and methanol, the manufacture of paper pulp, acid hydrolysis and the use of wood waste for plastics industry are indicated, although they are not considered immediately or widely applicable in this region. It is also pointed out that the economics of any undertaking on chemical wood utilization can be best ensured if such is integrated with one or other of the major wood using industries like saw-milling, plywood manufacture, etc. Also it seems that except for the very specialized chemical industries, the pioneer undertakings in the methods of chemical utilization of wood waste suggested here would have to be initiated as State enterprise, in order to demonstrate their economic prospects to the rather conservative industrialists of the country.